Single supplementation of goat colostrum, probiotics, and prebiotics for diarrhea management in cats - Dwi Budiono; Heryudianto Vibowo; Henny Endah Anggraeni; Anisa Rahma; Tekad Urip Pambudi Sujarnoko; Amaq Fadholly; Pradnya Calista; Hendri Zonathan; Kukuh Amru Dhiya Rahmat; Ivan Taufiq Nugraha (ARSHI Veterinary Letters, 2024)
Diarrhoea in cats is a change in the condition of faeces from paste to liquid consistency caused by several factors, such as food changes and bacterial, viral, and parasitic infections. Handling diarrhoea in cats is performed immediately so that the symptoms subside. One effective prevention and control effort is the provision of colostrum-based supplements, probiotics and prebiotics. In a case of diarrhoea at the Depok Pet Center clinic, two cats aged 1.5 years (Ayu) and 5 years (Gentong) were given colostrum-based supplements, probiotics, and prebiotics. The initial symptoms of the Ayu cat were diarrhoea and liquid faeces, while the Gentong cat had decreased appetite, weakness, and paste-shaped faeces. Supplementation was carried out for two days. On day three, the condition of the faeces of both cats were solid and shaped, but some parts of the faeces were still mushy. On day six, the condition of the faeces of both cats was good, marked by being shaped and solid.